Mechanism of microplastics in the reduction of cadmium toxicity in tomato - Rongchao Yang; Long Cheng; Zhenqin Li; Yilan Cui; Jiawei Liu; Duo Xu; Sijia Liu; Zhong Lin; Jiugeng Chen; Yueqin Zhang (Ecotoxicology and Environmental Safety)
Soil pollution by microplastics (MPs) and cadmium (Cd) poses significant threats to agricultural production, yet their combined toxicity and underlying mechanisms remain poorly understood. Here, we examined the effects of three types of MPs-polyethylene (PE), polyvinyl chloride (PVC) and polypropylene (PP)-with particle sizes of 150 μm and 10 μm, in combination with Cd stress (5 mg/kg) on tomato (Solanum lycopersicum L.) growth. The results revealed that the combined treatment of MPs effectively alleviated the inhibitory effect of Cd stress. Moreover, Ionome analysis demonstrated that the combined treatment alleviated ionic toxicity by reducing the accumulation of heavy metals (e.g., Al, Pb, Cd, Cr), restoring the uptake of essential elements (e.g., Mg, Ca, Mn), and minimizing the excessive absorption of trace elements (e.g., Mo, Ni) and ultra-trace elements (e.g., Co, Ag, Sn) compared to Cd stress alone. Transcriptome analysis further revealed that combined treatment reprogrammed key pathways, including cell wall synthesis, antioxidant systems, Cd transport, hormone signaling, nitrogen metabolism, and glutathione metabolism, to alleviate Cd toxicity. This study provides novel insights into the interaction between MPs and environmental pollutants, highlighting their role in modulating plant stress responses.